Prevalence of work related musculoskeletal disorders among canteen staff of Kathmandu University - Shakya, Nishchal Ratna; Shrestha, Shreya (Journal of Kathmandu Medical College, 2018)
Background: Work related musculoskeletal disorders are common complaint at workplace and is a leading cause of illness. A kitchen worker’s work consists of continuous long standing hours, awkward positions, lifting heavy loads and repetitive activities. The prevalence of musculoskeletal disorders is related to demographic factors, occupational, psychosocial factors and ergonomic risk factors at workplace. Canteen staffs are considered to be at higher risk of having musculoskeletal disorders.Objectives: To evaluate the prevalence of work related musculoskeletal disorders among the canteen staffs of Kathmandu University and to find association between risk factor and musculoskeletal disorders among the canteen staffs.Methodology: We carried out a cross-sectional descriptive study interviewing 40 participants for filling the demographic data and the standardized Nordic questionnaires for assessing the prevalence of musculoskeletal disorders among the canteen staffs of Kathmandu University. Data were analyzed using Statistical Package for the Social Sciences version 16.Results: We found that out of 40 participants, 60% reported having at least one work related musculoskeletal symptoms in the past 12 month. Back pain (35%) was most commonly reported disorder followed by neck (27.5%) and ankle pain (27.5%).Conclusion: Prevalence of work related musculoskeletal disorder among the canteen staffs of Kathmandu University was found to be high. So it is essential to take necessary steps to minimize musculoskeletal disorder and develop preventive strategies.